2007
DOI: 10.1109/tii.2007.898469
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Gait Planning for Pushing Motion of Humanoid Robot

Abstract: This paper describes real-time gait planning for pushing motion of humanoid robots. This method deals with an object whose mass is not known. In order that a humanoid robot pushes an unknown object in both single support phase and double support phase, real-time gait planning for pushing the unknown object is proposed. Real-time gait planning consists of zero moment point (ZMP) modification and cycle time modification. ZMP modification is the method that modifies the influence of reaction force to ZMP. By cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The dynamic stability of a humanoid robot under an external force has also been treated in the case where the humanoid robot is walking (Harada et al, 2004;Komura et al, 2005;Motoi et al, 2007). Sustaining the dynamic stability during walking is more difficult than during standing because both the walking itself and the external force disturb the stability of the humanoid robot.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic stability of a humanoid robot under an external force has also been treated in the case where the humanoid robot is walking (Harada et al, 2004;Komura et al, 2005;Motoi et al, 2007). Sustaining the dynamic stability during walking is more difficult than during standing because both the walking itself and the external force disturb the stability of the humanoid robot.…”
Section: Introductionmentioning
confidence: 99%
“…Pratt et al 17 suggested a capture point to compensate for and stabilize a biped robot in a sudden angular velocity situation by using the step out strategy. Motoi et al 18 suggested real-time gait planning for the pushing motion of a humanoid robot by using the inverted pendulum model. Harada et al 19 designed a walking motion to manipulate the pushing motion to a humanoid robot.…”
Section: Introductionmentioning
confidence: 99%
“…Using GP, it is difficult to develop optimal polynomial models for time-varying systems whose structures or coefficients vary over time while the diversity of individuals in a population is low. Timevarying characteristics can commonly be found in many industrial systems [6,22,41,44,57,66,36,34]. To develop models for time-varying environments, Wagner et al [60] developed a GP approach in which a varying window for capturing significant time series is proposed to generate time series models based on time series data.…”
Section: Introductionmentioning
confidence: 99%